Evaluation of hypolipidemic activity of homeopathic drug Allium sativum 6C potency on different grades of dyslipidemia in Wistar albino rat models - Thangarajeswari Mohan; Kalaiselvi Periandavan; Debadatta Nayak (Elsevier, 2022)
Background: Unhealthy dietary patterns and lifestyle modification could exacerbate heart-related diseases, and the risk factors for cardivascular disease mortality includes dyslipidemia, hypertension, and diabetes mellitus. However, controlling cholesterol, triglycerides, and low-density lipoprotein could minimize the occurrence of risk factors. Although homeopathic preparation of Allium sativum is effective in treating various ailments, it's therapeutic usage by the homeopathic practitioners must be validated scientifically to ascertain its action. Objectives: The present study is designed to evaluate the hypolipidemic and anti-inflammatory activities of the homeopathic drug A. sativum 6C in mitigating dyslipidemic changes in different types of dyslipidemic rat models. Methods: Assessment of serum biochemical parameters, evaluation of liver cytokines, and immunoblot analysis of inflammatory proteins were performed in this study. Results: Administration of a homeopathic preparation of A. sativum 6C to different types of dyslipidemic rat model showed a significant improvement in the serum lipid profile, reduction in the activity of serum marker enzymes (AST, ALT, LDH, and ALP), and decrement in the levels of liver inflammatory cytokines (TNFα, IL-6, and IL-1β). Further, the expression of inflammatory proteins (CRP, P-Selectin, E- Selectin) down regulated in the liver of dyslipidemic animals upon administration of A. sativum 6C. However, among the various dyslipidemic models, the efficacy of A. sativum is more profound in the HCD and HFD-fed animals. Analyzing the GC-MS data of A. sativum 6C revealed that it contains some active ingredients (Undecane; 1-methylene 1H-Indene, and Oxazolam) that might be responsible for the anti-inflammatory properties of A. sativum 6C. Conclusion: Homeopathic preparation of A. sativum 6C modulates the levels of serum biochemical parameters and inflammatory events in HCD-T and T2DM-T animals than in the STZ-T animals, mitigating metabolic dysfunction. Therefore, this study brings limelight to support the potency of the homeopathic drug A. sativum for therapeutic purposes in correcting metabolic dysfunction associated with the current lifestyle.